The Efficacy of Glass-Ceramic Onlays in the Restoration of Morphologically Compromised and Endodontically Treated Molars - TAĞTEKİN, DİLEK; YANIKOĞLU, FUNDA (QUINTESSENCE PUBLISHING CO INC, 2013)
Purpose: This study evaluated the 4-year clinical performance of IPS Empress II ceramic onlay restorations on extensively restored, endodontically treated molars. Materials and Methods: A sample of 53 morphologically compromised and endodontically treated molar teeth were restored with IPS Empress II ceramic onlays cemented with a dual-cured luting composite. The molars were evaluated by two experienced clinicians in accordance with the modified United States Public Health Service criteria at baseline and 6-month recalls up to a 4-year observation period. The analyses were carried out using the Wilcoxon signed-rank test and the Kaplan-Meier product limit method. Results: Four failures were noted. Two onlays debonded; one was reinserted and reluted while the other resulted in lost coronal hard tissue and was restored with a fiber-reinforced post-and-core system followed by a full ceramic crown restoration. The third failure resulted from secondary caries and fracture of the remaining enamel and was restored with a full ceramic crown. The fourth failure was extracted. None of the onlays exhibited wear, fracture of antagonist teeth, or dimensional change at proximal contacts. Conclusion: Within the limitations of this study's design and short 4-year observation period, IPS Empress II ceramic onlay restorations demonstrated promising results with a 92.5% success rate.
Keywords: CORONAL LEAKAGE; POST; INLAYS